Nationalism in Late and Post-Communist Europe: Volume 1 - The Failed Nationalism of the Multinational and Partial National States - Jahn, Egbert, (Nomos Verlagsgesellschaft mbH & Co. KG, 2008)
The age of nationalism has often been declared a bygone era. But it is by far not at its end. In the years 1990-93, more nation states than ever before came into being within a short period of time: 15 hybrid ethno-national states and three fragile states of federated nations. Since then, of the latter the Federal Republic of Yugoslavia fell apart, the two others are imperilled by ethno-national movements. State and ethnic nationalism have combined in each country in curious forms, allowing here and there for a gradual national consciousness, which aims at multinational federalism or national autonomy as an alternative to national secession.In this volume, authors from the East and the West discuss the results of many years of research on nationalism, as well as new approaches to the understanding of the nation. In addition, the failure of the multinational states Soviet Union, Yugoslavia, of the partial national state GDR, and presumably also Bosnia and Herzegovina, is analysed. After the breakdown of the multinational states and the polyethnic empires some decades ago, the question is raised if an integrating European Union will succeed in finding an adequate answer to nationalism and the nationalities problem.